PENINGKATAN PEMAHAMAN SISWA KELAS 5 TENTANG SISTEM PERNAPASAN MANUSIA MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MEDIA KONKRIT 3D - Firda Amalia; Ulhaq Zuhdi; Anna Sofiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This Class Action Research aims to improve the understanding of grade 5 students about the human respiratory system through the application of the Problem Based Learning (PBL) learning model with 3D concrete media of respiratory organs. The background of this research is the low understanding of students about abstract respiratory system material. The use of PBL models is expected to encourage students to actively solve problems related to the respiratory system, while 3D media of respiratory organs can help students visualize the concepts learned. The research method used is Classroom Action Research with two cycles. In each cycle, planning, implementation of actions, observation. Data collection instruments include learning outcome tests, observation sheets of student and teacher activities, and interviews. Data analysis is carried out quantitatively and qualitatively. The results show that the application of the PBL model with 3D media of respiratory organs can improve the understanding of grade 5 students about the human respiratory system. In the first cycle, the average student learning outcome score reached 75, and increased to 85 in the second cycle. In addition, student learning activities also increased from the category of